Import of health care services from India: Is it complementary to or substitute of the National Health Service of Bangladesh? - Hasan, Abu Hena Reza; Naim, Sayada Jannatun (IOSR Journal of Economics and Finance (IOSR-JEF), 2022)
This article was published in The IOSR Journal of Economics and Finance (IOSR-JEF) and the definite version is available at: DOI: 10.9790/5933-1006061015 The Article's website is at: https://www.iosrjournals.org/iosr-jef/papers/Vol10-Issue6/Series-6/B1006061015.pdf